Prosecuting Mass Atrocities at the Extraordinary Chambers in the Courts of Cambodia (ECCC) - Andrew T. Cayley (Washington University Global Studies Law Review, 2012)
After a lapse of nearly a quarter century, the United Nations and the Cambodian government agreed in 2003 to establish a hybrid internationalised domestic tribunal in an effort to address the legacy of impunity left in the wake of the Khmer Rouge regime. Several features make the Khmer Rouge Tribunal a unique experiment in international justice. It is the first internationalised court to seat a majority of judges from the affected nation. It is the first hybrid court to be established using a primarily civil law framework. Consequently, it was also the first to accord a central role to victims, who can join the proceedings as civil parties.
Keywords: extraordinary chambers in the courts of cambodia; cambodia; united nations